Tea industry's sustainable development: based on participants' tripartite evolutionary game and numerical simulation. (14th June 2022) - Chen, Yihui; Hong, Biyun
Based on the assumptions of bounded rationality and information asymmetry, this paper adopts the tripartite evolutionary game and the numerical simulation to analyse the evolutionary stable strategies and evolution process of the three participants in the sustainable development of the tea industry. Firstly, this paper makes reasonable assumptions based on reality and constructs the tripartite evolutionary game model that includes the government, the enterprises/farmers and consumers as the main participants. Secondly, this paper applies the Lyapunov stability discriminant equations to analyse the asymptotic stability of the equilibrium points in the tripartite evolutionary game model, and proves that when the constraints are met, there are four dynamic evolutionary stable strategies for the three participants. Thirdly, through further analysis and numerical simulation of each dynamic ESS, this paper confirms that under some constraints, it is more likely to achieve the sustainable development of the tea industry.